Real-world abdominal aorta aneurysm screening patterns among patients with new or worsening of symptomatic peripheral artery disease. (15th March 2023) - Lee, Megan; Pichert, Matthew D.; Tran, Andy T.; Farooq, Awais; Heyligers, Jan M.; de Vries, Jean-Paul P.M.; Spertus, John A.; Guzman, Raul J.; Thomas, Merrill; Mena-Hurtado, Carlos I.; Smolderen, Kim G.
Abstract: Background: Patients with peripheral artery disease (PAD) have an increased risk of abdominal aortic aneurysms (AAA), but it remains unclear whether practitioners are screening patients for AAA as part of routine PAD management. Methods: The Patient-centered Outcomes Related to Treatment Practices in Peripheral Arterial Disease (PORTRAIT) Registry is an international prospective registry of patients with new or worsening PAD symptoms presenting to 16 specialty centers in the United States, Netherlands, and Australia, from June 2011 to December 2015. Patients were stratified by AAA screening or AAA positivity. An adjusted median odds ratio was calculated for AAA screening rates across sites. Results: Of the 1275 patients in the study, 871 (68%) were screened for AAA, with 53 (6.1%) having AAA. AAA screening rates did not differ significantly by country ( p = 0.36), but there was a large variation across sites for documentation of AAA screening with an adjusted median odds ratio 12.0 (95% CI 4.7–93.1), with AAA screening rates ranging from 7% to 100% across vascular specialty centers. Conclusions: Among patients with PAD in a multicenter registry, over two-thirds were screened for AAA, with 6% having documented aneurysms. A large variation was seen across clinical sites, suggesting efforts are needed to increase awareness for guideline implementation and establish new benefit-risk evidence inclusive of high-risk populations such as patients with PAD. Highlights: Patients with peripheral artery disease (PAD) have an increased risk of abdominal aortic aneurysms. The international prospective PORTRAIT Registry has patients with new or worsening PAD symptoms. Abdominal aortic aneurysm screening rates in patients with PAD differed significantly across sites.